Faktor–Faktor Yang Berhubungan Dengan Perilaku Konsumsi Fast Food Pada Siswa SMA - Zalita Azwalika Octaviani; Indah Safitriani (AKPER Pasar Rebo, 2022)
Fast food is a dish that is practical and easy to process by containing high fat, high salt but low fiber. The purpose of this study was to determine the factors related to the consumption behavior of fast food in students at SMA Negeri 64 Jakarta in 2020. This study used a quantitative research method with a cross sectional research design using a research instrument in the form of a questionnaire. The total population in this study was 500 respondents and the total sample used in this study was 226 respondents. The results in this study are there is a relationship between the influence of peers (p value = 0.000), pocket money (p value = 0.000) and parental support (p value = 0.027) with fast food consumption behavior (fast food) in high school students. Negeri 64 Jakarta Year 2020. It is concluded that there is a relationship between the influence of peers, pocket money, parental support and consumption behavior of fast food. So it is suggested that it is necessary to disseminate information to parents at school to control pocket money and always bring provisions for students to school, as well as hold health education activities for students about consuming fast food and healthy foods with balanced nutrition.